Molt in Neotropical birds : life history and aging criteria - Johnson, Erik I.; Wolfe, Jared D. (Boca Raton : Taylor & Francis, 2017)
"Molt is an important avian life history event in which feathers are shed and replaced. The timing, duration, seasonality, extent and pattern of molt follows certain strategies and this book reviews and describes these strategies for nearly 190 species based on information gathered from a 30-year study of Central Amazonian birds. Most species accounts are illustrated with several color photos focusing on wing and tail feather molt, molt limits, and how to use these patterns to accurately age birds. The book will be a rich source of life history information for ornithologists working on tropical birds."--Provided by publisher.
part, 1 Overview of the Guide / Erik I. Johnson Jared D. Wolfe -- chapter 1 Introduction to This Guide / Erik I. Johnson Jared D. Wolfe -- chapter 2 How to Use This Guide / Erik I. Johnson Jared D. Wolfe -- part, 2 Non-passerine Land Birds / Erik I. Johnson Jared D. Wolfe -- chapter 3 Tinamidae (Tinamous) / Erik I. Johnson Jared D. Wolfe -- chapter 4 Odontophoridae (New World Quails) / Erik I. Johnson Jared D. Wolfe -- chapter 5 Accipitridae (Hawks, Kites, Eagles, and Allies) / Erik I. Johnson Jared D. Wolfe -- chapter 6 Psophiidae (Trumpeters) / Erik I. Johnson Jared D. Wolfe -- chapter 7 Columbidae (Pigeons and Doves) / Erik I. Johnson Jared D. Wolfe -- chapter 8 Cuculidae (Cuckoos, Roadrunners, and Anis) / Erik I. Johnson Jared D. Wolfe -- chapter 9 Strigidae (Typical Owls) / Erik I. Johnson Jared D. Wolfe -- chapter 10 Nyctibiidae (Potoos) / Erik I. Johnson Jared D. Wolfe -- chapter 11 Caprimulgidae (Nighthawks and Nightjars) / Erik I. Johnson Jared D. Wolfe -- chapter 12 Trochilidae (Hummingbirds) / Erik I. Johnson Jared D. Wolfe -- chapter 13 Trogonidae (Trogons) / Erik I. Johnson Jared D. Wolfe -- chapter 14 Alcedinidae (Kingfishers) / Erik I. Johnson Jared D. Wolfe -- chapter 15 Momotidae (Motmots) / Erik I. Johnson Jared D. Wolfe -- chapter 16 Galbulidae (Jacamars) / Erik I. Johnson Jared D. Wolfe -- chapter 17 Bucconidae (Puffbirds) / Erik I. Johnson Jared D. Wolfe -- chapter 18 Capitonidae (New World Barbets) / Erik I. Johnson Jared D. Wolfe -- chapter 19 Ramphastidae (Toucans) / Erik I. Johnson Jared D. Wolfe -- chapter 20 Picidae (Woodpeckers, Piculets, and Allies) / Erik I. Johnson Jared D. Wolfe -- chapter 21 Falconidae (Falcons) / Erik I. Johnson Jared D. Wolfe -- part, 3 Passerines, the Suboscines / Erik I. Johnson Jared D. Wolfe -- chapter 22 Thamnophilidae (Antbirds) / Erik I. Johnson Jared D. Wolfe -- chapter 23 Conopophagidae (Gnateaters and Pittasoma Antpittas) / Erik I. Johnson Jared D. Wolfe -- chapter 24 Grallariidae (Antpittas) / Erik I. Johnson Jared D. Wolfe -- chapter 25 Formicariidae (Antthrushes) / Erik I. Johnson Jared D. Wolfe -- chapter 26 Furnariidae (Ovenbirds, Leaftossers, and Woodcreepers) / Erik I. Johnson Jared D. Wolfe -- chapter 27 Tyrannidae (Tyrant Flycatchers and Allies) / Erik I. Johnson Jared D. Wolfe -- chapter 28 Cotingidae (Cotingas and Allies) / Erik I. Johnson Jared D. Wolfe -- chapter 29 Pipridae (Manakins) / Erik I. Johnson Jared D. Wolfe -- chapter 30 Tityridae (Tityras) / Erik I. Johnson Jared D. Wolfe -- part, 4 Passerines, the Oscines / Erik I. Johnson Jared D. Wolfe -- chapter 31 Vireonidae (Vireos) / Erik I. Johnson Jared D. Wolfe -- chapter 32 Hirundinidae (Swallows) / Erik I. Johnson Jared D. Wolfe -- chapter 33 Troglodytidae (Wrens) / Erik I. Johnson Jared D. Wolfe -- chapter 34 Polioptilidae (Gnatwrens and Gnatcatchers) / Erik I. Johnson Jared D. Wolfe -- chapter 35 Turdidae (Thrushes) / Erik I. Johnson Jared D. Wolfe -- chapter 36 Thraupidae (Tanagers) / Erik I. Johnson Jared D. Wolfe -- chapter 37 Emberizidae (Sparrows) / Erik I. Johnson Jared D. Wolfe -- chapter 38 Cardinalidae (Cardinal Grosbeaks, Piranga Tanagers, and Allies) / Erik I. Johnson Jared D. Wolfe -- chapter 39 Parulidae (Wood-Warblers) / Erik I. Johnson Jared D. Wolfe.
Keywords: Birds -- Amazon River Region; Feathers -- Amazon River Region; Molting